the Analysis of the Creativity Level of Mathematics Education Students in Basic Statistics Courses: Analisis Tingkat Kreativitas Mahasiswa Pendidikan Matematika pada Mata Kuliah Statistika Dasar - Nosva Adam Yunus; Suhardiman Darson Tamu; Febiyanti R. Hasan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the creativity level of Mathematics Education students at Muhammadiyah University Gorontalo in the Basic Statistics course. Creativity is understood as the ability to think divergently, which plays a role in mastering mathematical concepts and applying ideas in real contexts. The method used is a descriptive quantitative approach with a sample of 13 students selected purposively. Data were obtained through a creativity questionnaire based on Torrance's four indicators, namely fluency, flexibility, originality, and elaboration. The instrument used a 1–5 Likert scale, with categories: 1 = strongly disagree, 2 = disagree, 3 = unsure, 4 = agree, and 5 = strongly agree. The data were analyzed using descriptive statistics and the Kolmogorov–Smirnov and Shapiro–Wilk normality tests with the help of SPSS 26. The results showed that 2 students (15.4%) were in the low category, 7 students (53.8%) were in the medium category, and 4 students (30.8%) were in the high category with an average of 58.1%. The Kolmogorov–Smirnov significance value was 0.093 and the Shapiro–Wilk value was 0.238 (> 0.05), indicating that the data were normally distributed. These findings confirm that student creativity is in the moderate category and needs to be improved, especially in terms of flexibility of thinking and originality.